Differential effects of acute hyperglycemia and amyloid‐beta pathology on sleep and cerebral metabolism. (1st February 2022) - Carroll, Caitlin M; Stanley, Molly; McArdle, Colin; Snipes, Andy; Gould, Rob; Macauley, Shannon L
Abstract: Background: While both metabolic and sleep disruptions are implicated in Alzheimer's disease (AD), there are no clearly defined mechanisms connecting these factors as driving forces in early pathophysiology. Previous work in the lab showed acute hyperglycemia increases cerebral metabolism, neuronal activity, and amyloid‐beta (Aβ) levels in the hippocampus, all factors that can negatively impact sleep. Moreover, this effect was exacerbated by the presence of Aβ pathology. The goal of this study is to identify metabolic dysregulation as a causal factor in the bidirectional relationship between sleep and AD, thereby contributing to increased risk of Aβ plaque development and AD onset. Method: Biosensors detecting interstitial fluid (ISF) glucose and lactate are implanted bilaterally into the hippocampi of wildtype (WT) and APP/PS1 mice, a model of Aβ pathology overexpression. Glucose represents a measure of cerebral metabolism, while lactate is a biomarker of neuronal activity. Biosensors are paired with cortical EEG/EMG recordings for sleep staging. Mice are exposed to high fat diet and high sugar water (HFD) for 72‐hours to determine how a peripheral metabolic challenge impacts cerebral metabolism and sleep both independent of, and as a function of Aβ pathology. Result: In 3‐month‐old WT mice, ISF glucose increases in response to HFD, without changing peripheral blood glucose levels. This is accompanied by increased time spent awake and spectral power changes consistent with decreased sleep efficiency and propensity compared to mice fed normal chow. In 9‐month‐old APP/PS1 mice with Aβ deposition and baseline sleep disruptions, the effects on sleep are intensified. Moreover, preliminary results show that while both HFD and Aβ deposition decrease total sleep, sleep quality is affected differentially, as indicated by distinct shifts in spectral power. Conclusion: This study represents a novel approach to understanding the dynamic interplay between AD risk factors. Our data shows acute exposure to peripheral hyperglycemia can have profound effects on brain metabolism and sleep homeostasis, effects amplified by the presence of Aβ. By identifying disrupted metabolism as a modifiable risk factor contributing to early changes in sleep and cerebral metabolic functioning, more specific therapeutics can be developed to mitigate increased AD risk for individuals with metabolic and sleep disorders.